Correlation analysis of serum endothelial cell specific molecule-1, endothelial microparticles, hypoxia inducible factor-1α levels and acute myocardial infarction and their predictive value for major adverse cardiovascular events: a retrospective study - Zhang,Qiubing; Xu,Zhe; Shi,Ping; Zeng,Jia; Yin,Xiaohong; Gou,Fang (PeerJ, 2025)
Objective This study aimed to analyse the correlation of endothelial cell specific molecule-1 (ESM-1), endothelial microparticles (EMPs) and hypoxia inducible factor-1α (HIF-1α) serum levels with the occurrence of acute myocardial infarction (AMI) and determine their short-term predictive value for major adverse cardiovascular events (MACE) following AMI treatment. Methods Retrospective data analysis was performed on the medical records of 106 patients with AMI admitted to our hospital between October 2020 and October 2022. The control group consisted of 106 healthy volunteers that received a physical examination at our hospital’s physical examination centre within the same time frame. ESM-1, EMP and HIF-1α serum levels were compared between the two groups. Independent risk variables for AMI were examined. Furthermore, these individuals were separated into the poor prognosis group (n = 41) and good prognosis group (n = 65) according to the presence or absence of MACE. Finally, the ESM-1, EMPs and HIF-1α serum levels were correlated with the development of MACE in patients with AMI, and the predictive value of serum ESM-1, EMPs and HIF-1α for MACE was evaluated. The serum HIF-1α, EMP and ESM-1 levels were significantly different between the two groups (P < 0.05). Multivariate logistic regression analysis revealed the elevated serum levels of HIF-1α (odds ratio (OR) = 1.819), EMPs (OR = 1.071) and ESM-1 (OR = 14.655) as AMI risk variables. A substantially significant (P < 0.05) correlation was found between the elevated levels of serum HIF-1α (OR = 18.716), EMPs (OR = 26.185) and ESM-1 (OR = 13.992) and the development of MACE in patients with AMI. According to receiver operating characteristic (ROC) curve analysis, the combined evaluation value of HIF-1α, EMPs and ESM-1 serum levels in predicting MACE was high with an area under the curve (AUC) of 0.931. Conclusion Patients with AMI have abnormally high ESM-1, EMP and HIF-1α levels in their serum, all of which have been linked to the development of MACE. Together, these parameters have high sensitivity and specificity for early MACE identification.
Keywords: Serum; Hypoxia inducible factor-1α; Endothelial cell specific molecule-1; Endothelial microparticles; Acute myocardial infarction; Predictive value